ANALISIS TINGKAT KEPUASAN PELANGGAN PADA RUDANG HOTEL BERASTAGI MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX (CSI) - Okta Jaya Harmaja; Windania Purba; Maxwell Paulus Siregar; Henry Triadi Manurung; Fransisco Andreas Sirait (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Service quality is very important in the hospitality industry because of the great competition in the industry. Therefore, the hotel must provide the best service to its guests. This study was conducted to see how the quality of service at the Rudang Berastagi hotel to guests using the CSI method to calculate the level of customer satisfaction at the Rudang Berastagi Hotel as an evaluation material to improve hotel services in the future. Data processing in this study was carried out using the Python programming language through Google Colab. Based on the calculation of guest satisfaction at Rudang Berastagi Hotel through a questionnaire of 110 respondents, it was found that the guests were satisfied with the services provided by Rudang Berastagi Hotel with a satisfaction level of 78.4% using the Customer Satisfication Index (CSI) method. According to the questionnaires that have been distributed, it is concluded that question number 1 with the contents of the questions having a complete, comfortable, clean, and well-organized room interior gets the highest mean value of 4.27%.